A guide to data cleaning using Stata - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
In order to provide a comprehensive view of the multiple stages involved in a rigorous data cleaning process, this manual is divided into four chapters. Chapter 1 starts by listing the terms and definitions which the user is expected to be familiar with. Then, it provides the motivation for using Stata in general but also for performing data cleaning in particular. It concludes with a description of the basic syntax and commands in Stata. Chapter 2 provides an overview of the strategies used in the cleaning of string variables. Chapter 3 focuses on numeric variables and the various ways to label, describe, clean, analyze, detect and correct problems. Chapter 4 combines all the pieces together and presents a strategy to data cleaning.